2015
DOI: 10.17116/neiro201579428-37
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of large and giant intracranial aneurysms using stent assistance

Abstract: Stent assistance enables achieving total or subtotal occlusion of large and giant aneurysms in 90% of cases. In certain clinical situations, it is an alternative to other existing methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…With the application of covered stents, it has become possible to protect the parent artery and promote endovascular remodeling. 30,31 Based on the results obtained from our study, covered stents appear to have certain efficacy in the treatment of such lesions.…”
Section: Discussionmentioning
confidence: 71%
“…With the application of covered stents, it has become possible to protect the parent artery and promote endovascular remodeling. 30,31 Based on the results obtained from our study, covered stents appear to have certain efficacy in the treatment of such lesions.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, endovascular treatment for MCA aneurysms decreased the morbidity and mortality rates compared with those achieved by conventional clipping, which suggested that combined treatment by endovascular and bypass surgery is capable of efficiently treating giant complex fusiform MCA aneurysms (14). Of note, a previous study has indicated that stent assistance contributed to the beneficial effect of endovascular treatment of MCA aneurysms, and identified that stent assistance achieves total or subtotal occlusion of large and giant aneurysms in 90% of cases (15).…”
Section: Introductionmentioning
confidence: 99%
“…Эндоваскулярные методи-ки позволяют выключить аневризмы из кровообра-щения и значительно снижают риск внутричереп-ного кровоизлияния, но имеют и некоторые недо-статки, такие как неполная окклюзия и отсроченная реканализация аневризмы, а также тромбоз уста-новленного стента [24][25][26]. Важной особенностью эндоваскулярных вмешательств является сохране-ние или нарастание объемного воздействия, об-условленного в раннем послеоперационном перио-де увеличением размеров аневризмы вследствие тром-боза, на прилежащие нервные структуры с нарастани-ем неврологического дефицита [1,6,8,15,16,21].…”
Section: Discussionunclassified